2005
DOI: 10.4161/auto.1.2.1737
|View full text |Cite
|
Sign up to set email alerts
|

Pexophagy: The Selective Autophagy of Peroxisomes

Abstract: Pichia pastoris and Hansenula polymorpha are methylotrophic yeasts capable of utilizing methanol, as a sole source of carbon and energy. Growth of these yeast species on methanol requires the synthesis of cytosolic and peroxisomal enzymes combined with the proliferation of peroxisomes. Peroxisomes are also abundantly present in the alkane-utilizing yeast Yarrowia lipolytica upon growth of cells on oleic acid. This feature has made these yeast species attractive model systems to dissect the molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(74 citation statements)
references
References 56 publications
(82 reference statements)
0
70
1
Order By: Relevance
“…Thus the UPR may function in conjunction with ER-phagy to balance ER synthesis with ER degradation as part of the homeostatic control network that adjusts ER abundance up and down. Similarly, pexophagy degrades excess peroxisomes when cells switch carbon sources from using fatty acids to other food stuffs [39,73], and mitophagy reduces mitochondrial abundance, e.g., under starvation conditions or under respiring conditions when mitochondria become easily damaged by oxygen radicals [40,74]. For pexophagy, Pex14 has been proposed to have a role in the selective targeting of peroxisomes for degradation [75], but how autophagy targets other organelles for selective sequestration remains an open question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the UPR may function in conjunction with ER-phagy to balance ER synthesis with ER degradation as part of the homeostatic control network that adjusts ER abundance up and down. Similarly, pexophagy degrades excess peroxisomes when cells switch carbon sources from using fatty acids to other food stuffs [39,73], and mitophagy reduces mitochondrial abundance, e.g., under starvation conditions or under respiring conditions when mitochondria become easily damaged by oxygen radicals [40,74]. For pexophagy, Pex14 has been proposed to have a role in the selective targeting of peroxisomes for degradation [75], but how autophagy targets other organelles for selective sequestration remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the early secretory pathway contributes to the assembly of autophagosomes [3638]. By contrast to macro-autophagy, pexophagy and mitophagy are highly selective processes that degrade an excess of peroxisomes and mitochondria, respectively, under growth conditions that change the requirement for these organelles [39,40]. It has been proposed that marker proteins are selectively displayed on no longer needed or damaged organelles, and direct their sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to bulk autophagy, selective autophagy involves targeted removal of damaged organelles, cellular debris, microorganisms, and pathogens (Reggiori et al, 2012). These special targets include mitochondria (mitophagy) (Youle and Narendra, 2011), peroxisomes (pexophagy) (Dunn et al, 2005), lysosomes (lysophagy) (Hung et al, 2013), lipid droplets (lipophagy) (Singh et al, 2009), secretory granules (zymophagy) (Grasso et al, 2011), the ER (reticulophagy) (Bernales et al, 2007), nucleus (nucleophagy) (Park et al, 2009), RNA (RNautophagy) (Fujiwara et al, 2013), pathogens (xenophagy) (Levine, 2005), ribosomes (ribophagy) (Kraft et al, 2008), and aggregate-prone proteins (aggrephagy) (Overbye et al, 2007). …”
Section: Hmgb1 and Cell Death (Figure 12)mentioning
confidence: 99%
“…The Cvt pathway is similar to macroautophagy except it happens in all conditions while macroautophagy occurs during starvation [14]. Several other forms of selective autophagy to degrade specific organelles have also been discovered, such as mitophagy for the autophagic degradation of mitochondria [15]; pexophagy for clearance of peroxisomes [16]; reticulophagy for the degradation of ER [17], and ribophagy for removal of ribosomes [18]. …”
Section: Autophagy In Saccharomyces Cerevisiaementioning
confidence: 99%